Identification of water stress in tomato based on spectral indices and physiological parameters - Thussagunpanit, Jutiporn; Tewathammanaj, Wanthanee; Thongyen, Phirada; Manochai, Benya; Chulaka, Pariyanuj (Agriculture and Natural Resources, 2025)
Importance of the work: Generally, farmers use a large amount of water to produce greenhouse cherry tomatoes, resulting in increased production costs and possibly suboptimal excessive water use. Objectives: To investigate the optimum water content for ‘Sweet Boy’ cherry tomato production, based on changes in tomato physiology and yield. Materials and Methods: A completely randomized design was used, consisting of four levels of pot water capacity (PC; 60%PC, 80%PC, 100%PC (the control) and 120%PC) as the water-holding level in the growing medium. Physiological responses and tomato yield in each treatment were measured. Results: Water levels of 60%PC and 80%PC decreased the tested spectral indices (the normalized difference vegetation index, the normalized difference red-edge index and the photochemical reflectance index). Furthermore, a water content of 60%PC significantly reduced the net photosynthetic rate (22.63–32.08%) and stomatal conductance (57.23–88.29%) in the vegetative and flowering stages compared to 100%PC. In addition, 100%PC achieved similar physiological and yield responses as 120%PC. After fruit harvest, 60%PC and 80%PC reduced the fruit weight and the total yield per plant. However, 60%PC produced significantly higher total soluble solids (9.48°Brix), ascorbic acid (9.11 mg/kg fresh weight, FW) and lycopene (4.24 mg/kg FW) contents than the control. Main finding: Irrigation at 100%PC and 120%PC produced similar physiological responses and yields in cherry tomato plants. Therefore, 100%PC irrigation reduced water use by 32% compared to the 120%PC treatment while maintaining high yield and acceptable fruit quality. It is recommended that farmers irrigate at 100%PC to optimize productivity and efficient water use.